2015
DOI: 10.1080/02640414.2015.1069376
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic analysis of lower limb muscles during the golf swing performed with three different clubs

Abstract: The aim of this study was to describe and compare the EMG patterns of select lower limb muscles throughout the golf swing, performed with three different clubs, in non-elite middle-aged players. Fourteen golfers performed eight swings each using, in random order, a pitching wedge, 7-iron and 4-iron. Surface electromyography (EMG) was recorded bilaterally from lower limb muscles: tibialis anterior, peroneus longus, gastrocnemius medialis, gastrocnemius lateralis, biceps femoris, semitendinosus, gluteus maximus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 24 publications
(41 reference statements)
0
23
1
Order By: Relevance
“…Contrary to the findings of the current study and Marta et al (2013), Marta et al (2015) displayed significant changes in muscle activity in the lower limb muscles when examining the 4-iron, 7-iron and pitching wedge. These contrasting results are likely to be a result of different muscles being examined within the study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to the findings of the current study and Marta et al (2013), Marta et al (2015) displayed significant changes in muscle activity in the lower limb muscles when examining the 4-iron, 7-iron and pitching wedge. These contrasting results are likely to be a result of different muscles being examined within the study.…”
Section: Discussioncontrasting
confidence: 99%
“…These contrasting results are likely to be a result of different muscles being examined within the study. Specifically, the significant changes observed in the study conducted by Marta et al (2015) could be associated with the hip extensor muscles requiring greater activation levels when the shaft length and CHS increases. Keogh et al (2009) have also shown CHS is significantly correlated with lower-body strength.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…To our knowledge, no studies have examined the activities of the PM during the downswing. However, an electromyographic analysis of lower limb muscles during the golf swing have shown that as compared with high-handicap golfers, low-handicap golfers had greater activation of the left rectus femoris (a hip flexor) to produce left hip flexion [26]. In light of the above findings, the left hip flexion rather than the right hip extension would be important for twisting the trunk to the left during the golf swing; thus, the degree of bilateral asymmetry of the PM might have been selected as a significant contributor for achieving faster CHS.…”
Section: Discussionmentioning
confidence: 99%